The disruptive triad and entrepreneurship: A theoretical model - Félix O. Socorro Márquez; Giovanni E. Reyes (Journal of Innovation and Entrepreneurship, 2021)
The main objective of this study is to propose a theoretical model to understand the importance of disruption-in three of its dimensions, thinking, creativity, and innovation-developed and applied in the thinking and exercise of entrepreneurship and, at the same time, highlight the relationship of the disruption with competitiveness. Being competitive is one of the most demanding goals that entrepreneurs can and should set themselves; however, unlike established or traditional companies, usually the entrepreneur cannot promote competitiveness in the same way that they do. Taking these into account, it is necessary to use unconventional tools, or a different perspective methodology, for promoting creativity and innovation beyond the entrepreneurial activity itself. Through a qualitative methodology, with an emphasis on documentary research and inferential and deductive reasoning, a theoretical model is proposed. The model seeks to illustrate how disruptive currents can help entrepreneurs to be more competitive and, at the same time, boost their entrepreneurial spirit.
Keywords: 650; Competitiveness; Creativity; Disruption; Innovation; Thinking; Entrepreneurship